2017
DOI: 10.11646/phytotaxa.306.3.6
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Paris sect. Axiparis (Melanthiaceae) from Yunnan, China

Abstract: Paris Linnaeus (1573: 367) is a temperate genus of about 27 species of perennial herbs distributed in Eurasia (Li 1998, Ji et al. 2007). Most species are restricted to East Asia, chiefly to China (19 species), with the Yunnnan-Guizhou Plateau in southwest China as the centre of species diversity (Li 1998). Paris is well known in China for its medicinal value. Those species with a thick rhizome have been used as medicinal herbs for more than 2,000 years in China owing to its analgesic, haemostatic, anti-tumor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…We sampled 33 accessions to represent all 29 species and five varieties recognized by Li [7] and those described since then [9, 84, 117119]. The original sources of the plant materials used in this study and voucher information are presented in Additional file 4: Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…We sampled 33 accessions to represent all 29 species and five varieties recognized by Li [7] and those described since then [9, 84, 117119]. The original sources of the plant materials used in this study and voucher information are presented in Additional file 4: Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is reasonable to recognized them as distinct species under the unified species concept (de Queiroz, 2007), given that the species boundary proposed by our data reflects the unity of morphological uniqueness, genetic distinctiveness, and evolutionary independence. The findings suggest that previous morphology-based taxonomic studies (Li, 1984;He, 1990;Li, 1992;Ji et al, 2017;Xu et al, 2019;Yang et al, 2019) overemphasize intraspecific and minor morphological differences to establish species, therefore leading to the proliferation of synonyms. As a result, it is necessary to reduce P. axialis , P. guizhouensis , P. lihengiana , and P. variabilis as the synonyms of P. vaniotii , and to merge P. dulongensis ,P. rugosa and P. tengchongensis into P. forrestii .…”
Section: Species Delimitation Scenariomentioning
confidence: 79%
“…For instance, among the nine nominal species of P.sect. Axiparis , P. dulongensis and P. lihengianaare categorized as critically endangered (Qin et al, 2017;Xu et al, 2019); P. forrestii , P. guizhouensis , P. rugosa ,P. tengchongensis and P. vaniotii are classified as endangered (Ji et al, 2017;Qin et al, 2017); P. axialis andP. variabilis are identified as Vulnerable (Qin et al, 2017;Yang et al, 2019).…”
Section: Conservation Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Paris comprises about 27 species accepted in The Plant List (http://www.theplantlist.org/) and divides into two subgenera, Paris and Daiswa (Huang et al 2016). In recent years, several new Paris species, such as P. lihengiana (Xu et al 2019), P. tengchongensis (Ji et al 2017) and P. nitida (Wang et al 2017) were reported. In this study, we constructed the phylogenetic tree and analyzed the phylogenetic position of P. delavayi based on the maximum likelihood (ML) and Bayesian inference (BI) methods (Ronquist et al 2012;Stamatakis 2014).…”
mentioning
confidence: 99%